Translating for the community - Taibi, Mustapha (Multilingual Matters, 2018)
This book offers rich insights into the practice of community translation. Chapters outline the specific nature and challenges of community translation, quality standards, training and the relationship between community translation as a professional practice and volunteer or crowd-sourced translation.
Keywords: Public service interpreting.; Translating and interpreting -- Social aspects.; Intercultural communication.; Interprétation communautaire (Traduction); Communication interculturelle.; Migration, immigration & emigration.; Sociolinguistics.; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks.; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; LANGUAGE ARTS & DISCIPLINES -- Readers.; LANGUAGE ARTS & DISCIPLINES -- Spelling.; Intercultural communication; Public service interpreting; Translating and interpreting -- Social aspects; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting